Soft Power in Turkey's Foreign Policy in Europe - Yakov Y. Grishin; Damir R. Islamov (Современная Европа)
Since the mid-2000s, under the rule of the Justice and Development Party, Turkey has included the concept of soft power in its foreign policy agenda. Based on the position of Turkish officials, the practical implementation of soft power is based on public diplomacy, with its “infrastructure” being created at the same time by establishing new or transforming existing state structures in partnership with non-governmental organisations. Ankara has developed the main directions for public diplomacy to be based on interaction with its Turkish people living abroad and closely related Turkic peoples, the preservation and revival of the cultural, historical and material heritage of the Ottoman Empire, and the support of the Muslim community in different parts of the world. In addition, in recent years, relatively new directions have emerged, such as struggling against FETÖ and extension of coverage of the Turkish Radio and Television Corporation. One of the regions where the Turkish public diplomacy was implemented was Europe. The latter was divided into three sub-regions: the Balkans, Eastern Europe, and Western Europe. The Balkan countries were traditionally considered important regions for Ankara with the core goal to break old historical and cultural prejudices about its image and to form a positive one in the eyes of the public. With regard to Eastern Europe, Turkey, skillfully using the Ottoman heritage and/or the Turkic factor, exerts influence in Hungary, Moldova, and Ukraine. And the activity in Western Europe is more based on interacting with the Turkish diaspora. Therefore, the aim of the study is to reveal the main directions of Turkey's public diplomacy in the context of the implementation of the policy of soft power in Europe.